2019
DOI: 10.3390/cryst9030167
|View full text |Cite
|
Sign up to set email alerts
|

Stimulated Raman Scattering in Alkali-Earth Tungstate and Molybdate Crystals at Both Stretching and Bending Raman Modes under Synchronous Picosecond Pumping with Multiple Pulse Shortening Down to 1 ps

Abstract: Comparative investigation of characteristics of spontaneous and stimulated Raman scattering (SRS) in different alkali-earth tungstate and molybdate crystals at both high and low frequency anionic group vibrations is presented. It has been found that, among these crystals, the SrMoO4 and SrWO4 crystals are the most perspective for SRS generation on both stretching and bending modes of internal anionic group vibrations with the strongest SRS pulse shortening under synchronous laser pumping because of not only hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 84 publications
1
20
0
Order By: Relevance
“…It is also necessary to pay attention to the observed effect of increasing slope efficiency of oscillation from 25.7% to 44.7% for PbMoO 4 and from 20.0% to 33.8% for PbWO 4 with the change of the pumping orientation from E || c to E ⊥ c that is accompanied by increase in the Raman gain with no change of losses. Earlier, similar effect was observed in many synchronously pumped Raman lasers based on GdVO 4 [28], SrWO 4 [18,29], and PbMoO 4 [19] active crystals via a change of the single-pass Raman gain by a change of the crystal length or pumping orientation. A possible explanation of the effect may be the action of synchronous pumping as it was proposed in work [19].…”
Section: Srs In Pbmoo 4 and Pbwosupporting
confidence: 71%
See 3 more Smart Citations
“…It is also necessary to pay attention to the observed effect of increasing slope efficiency of oscillation from 25.7% to 44.7% for PbMoO 4 and from 20.0% to 33.8% for PbWO 4 with the change of the pumping orientation from E || c to E ⊥ c that is accompanied by increase in the Raman gain with no change of losses. Earlier, similar effect was observed in many synchronously pumped Raman lasers based on GdVO 4 [28], SrWO 4 [18,29], and PbMoO 4 [19] active crystals via a change of the single-pass Raman gain by a change of the crystal length or pumping orientation. A possible explanation of the effect may be the action of synchronous pumping as it was proposed in work [19].…”
Section: Srs In Pbmoo 4 and Pbwosupporting
confidence: 71%
“…Figure 2 shows the experimental setup. It is similar to that used in the previous works [17][18][19] using other Raman-active crystals. The Raman laser with an external ring cavity based on each Raman-active crystal under study was synchronously pumped by repetitively pumped, 36-ps, 150-MHz, 330-nJ Nd:GdVO4 laser at a wavelength of λ0 = 1063 nm operating in quasi-continuous regime with the 500µ s. The pumping was single-pass due to high transmission of both concave mirrors (PM and CM) of the Raman laser cavity.…”
Section: Methodsmentioning
confidence: 67%
See 2 more Smart Citations
“…One of the promising applications of solitons is, of course, spectroscopy. The comparative investigation of characteristics of spontaneous and stimulated Raman scattering (SRS) in different alkali-earth tungstate and molybdate crystals at both high and low-frequency anionic group vibrations was presented, for example, in [10]. It has been found that, among these crystals, the SrMoO 4 and SrWO 4 crystals are the most perspectives for SRS generation on both stretching and bending modes of internal anionic group vibrations with the strongest SRS pulse shortening under synchronous laser pumping.…”
Section: Introductionmentioning
confidence: 99%